Derechos de propiedad y minería aurífera ilegal en la cuenca alta del río Nanay Loreto 2024 - Guzmán Urdanivia, Betty Mercy (2025)
The study, of a descriptive, correlational and transversal type, analyzes the relationship between property rights and illegal gold mining in the middle and upper basin of the Nanay River, based on 40 interviews carried out with leaders of seven local communities. Using structured surveys and statistical analysis with SPSS, it was determined that the clarity and accessibility of property titles are essential to deter illegal mining, while the lack of adequate documentation facilitates illicit exploitation, territorial conflicts and environmental deterioration. It is concluded that illegal mining has seriously affected traditional livelihoods, increased deforestation, mercury levels and the degradation of ecosystems, putting health and biodiversity at risk. In addition, it has generated insecurity and conflict in communities due to competition for resources and the presence of external actors. The recognition of communal titles and local autonomy are key to the conservation and reduction of illicit activities, by allowing the implementation of internal control mechanisms. Finally, it is evident that strengthening land tenure security and institutional presence would contribute to regulating illegal mining and improving social cohesion in the Nanay River basin.